Fluctuations and Business Cycles Prevention by New Financial Instruments and Banking Structure Reform - Bidabad, Bijan (International Journal of Accounting & Finance Review, 2019)
Regarding the formation of financial crises in monetary and financial markets of advanced economies and its transmission to other countries through financial markets and foreign trade, a solution is pointed out which is called the reform of financial, monetary and banking structure. In spite of various theories about the source of crises, studies in this field show that usurious banking structures are the main source of crises. The curing method of this economic disease is to prevent somehow the existing time-lag between “deposits interest rates” and “loans interest rates”, which creates fluctuations in supply and demand of financial sources. That is to say, banks should not function as a conventional economic firm, but should function as a financial intermediate. Banking structural reform and new financial instruments will be introduced in this regard.Profit and Loss Sharing (PLS) Banking and its sub-systems as Joaleh Financial Sharing (JFS) and Mudarebeh Financial Sharing (MFS) with new financial instruments of “Partnership (Mosharekah) Certificate”, “Subscripted (Pazireh) Certificates” and “Future Certificate” are introduced at commercial and specialized banking levels. “Interest-Free Bonds” in four different groups of “Central Bank Interest-free Bonds”, “Banking Interest-free Bonds”, “Treasury Interest-free Bonds” all in varieties on domestic money and Foreign Currency are also introduced which in addition to elimination of usury, can be efficiently used as secure financial instruments at central, commercial and retail banking levels. “Saving Qarzul-Hasanah Certificate” as a kind of Interest-Free Bonds are also introduced. Non-Usury Script-less Security Settlement System (NSSSS) based on information and communication technology has been put forward for creating a secondary market of financial instruments transaction which provides the necessary background for financial structure reform. Squandering prevention and waste prevention and economic ethic teachings are also introduced as supplements in solving crises.